The Aggregation of ATAD2 Bromodomain in Solution - WANG Yuanfang; WANG Xiaohua; SHU Chang; ZHANG Xu; LIU Maili; ZENG Danyun (Chinese Journal of Magnetic Resonance, 2023)
ATPase family AAA domain-containing protein 2 (ATAD2) is a chromatin regulator, also known as an oncogenic transcription cofactor. Its abnormal expression is closely related to the occurrence and development of various malignant tumors. ATAD2 consists of two domains: the ATPase domain and the bromodomain. The bromodomain can specifically recognize and interact with the acetylated lysines in proteins, which regulates the refactoring and transcription of chromosomes. In this work, we found that ATAD2 bromodomains are aggregated under normal solution conditions. Considering the possible impact of aggregation on the interaction between ATAD2 bromodomain and acetylated histone tail, we preliminarily investigated the aggregation of ATAD2 bromodomains mainly by nuclear magnetic resonance (NMR) and circular dichroism (CD) spectra. The results suggested that the aggregation is accompanied with structure alteration and possibly related to the physiological functions of cells. This study may provide new clues for the development of ATAD2 bromodomain inhibitors.